Cultural Pluralism and the Limitations of the Classicist Conception of Culture - St. Amour, Paul (Proceedings of the American Catholic Philosophical Association, 2003)
Bernard Lonergan has attempted to clarify a major theoretical transition from a classicist conception of culture, which was operative for over two millennia, to a contemporary notion of culture which is empirical, historicist, and pluralist. I argue that this transition has significant implications for apprehending both the difficulty and the possibility of intercultural understanding. While the need for intercultural understanding is timely and obvious, its actual achievement has proven elusive. One major impediment, I argue, has been the effective persistence of classicist assumptions which undermine our best theoretical understandings of what a culture is.